Philippe Lacoue-Labarthe : representation and the loss of the subject - Martis, John (Perspectives in continental philosophy ;, 2005)
John Martis introduces the range of French philosopher Philippe Lacoue-Labarthe's thinking, demonstrating the systematic nature of his philosophical project.